Desenvolvimento de curativo de celulose bacteriana oxidada incorporando papaína para o tratamento de lesões cutâneas - Vasconcelos, Niédja Fittipaldi (2020)
Dressings are an important segment of the medical and pharmaceutical market that motivates research into biomaterials capable of accelerating the healing process. In this context, bacterial cellulose (BC) is a biopolymer that has promising properties to act as a protective and control dressing on the wound. In addition, chemical modification of its structure may allow the covalent immobilization of enzymes that can actively act on the wound and aid in healing. In this work, BC membranes were used to develop an advanced bioactive papain-containing dressing, which is commonly employed as necrotic tissue debridement agent, capable of accelerating the healing of skin wounds. BC membrane was produced by static cultivation (5, 7 and 10 days of fermentation), purified by alkaline treatment (with NaOH or K2CO3) and oxidized with NaIO4 (reaction time: 6, 16 and 24 hours and temperature: 40 and 55 ºC). In order to optimize conditions for papain immobilization, an experimental design was performed, where the independent variables pH (3 to 7) and temperature (5 to 45 ºC) were evaluated. BC membranes obtained after 5 days of fermentation and purified with K2CO3 solution (called BC-5d-K2CO3) presented the most favorable conditions (higher porosity and surface area) for the development of passive dressing. The determination of BC-5d-K2CO3 membrane oxidation time and temperature established a favorable condition of 6 hours at 55 ºC (called OxBC-6-55) for chemical modification with NaIO4, providing a degree of oxidation of 50% and preserving the physicochemical properties of the starting membrane. The statistical effects of temperature and pH on immobilization yield, recovered activity and immobilized activity provided the optimal condition of papain immobilization on CBOx-6-55 at pH 7 and 45 ºC (called OxBC-Papain). To evaluate the efficiency of the supporting membranes, this optimal condition was used for papain immobilization on CB-5d-K2CO3 (called BC-Papain). OxBC-Papain (which represents the advanced bioactive dressing) showed a higher percentage of enzyme release than BC-Papain and exhibited adequate structural properties for a skin dressing. Non-cytotoxic effects (on epidermal cells) and non-hemolytic effects were observed in relation to membrane. Moreover, the dressing had hemostatic property and low cell adhesion, which are promising characteristics when compared to traditional dressings (cotton, bandages and gauze). Therefore, the dressing containing papain, developed from the BC membrane, resulted in a bioactive material with ideal in vitro properties for the treatment of epidermal lesions.